Analytic and numeric solutions for stagnation-point flow with melting, thermal-diffusion and diffusion-thermo effects. Issue 2 (25th February 2014) - Awais, M.; Hayat, T.; Mustafa, M.; Bhattacharyya, K.; Asif Farooq, M.
Abstract : Purpose: – The aim of this work is to analyze the combined effects of melting, thermal-diffusion and diffusion-thermo on the flow of non-Newtonian fluid. Design/methodology/approach: – An efficient approach namely homotopy analysis method is applied to compute the solution of the non-linear problem. Moreover, numerical results using MATLAB function bvp4c are also computed. Findings: – Main findings are an increase in the melting process corresponding to increase in the velocity and the boundary layer thickness. However, surface heat and mass transfer decrease by increasing the values of melting parameter M . Originality/value: – Combined effects of thermal-diffusion and diffusion-thermo are analyzed and the solutions are computed both numerically and analytically. Some deduced results can be obtained in a limiting sense.